2020
DOI: 10.31557/apjcp.2020.21.3.791
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of p53 and Its Target Gene Expression as Potential Biomarkers of Cholangiocarcinoma in Thai Patients

Abstract: Background: Cholangiocarcinoma (CCA), a common cancer in northeastern Thailand, is a severe disease with poor prognosis and short survival time following diagnosis. DNA damage in CCA is believed to be caused by liver fluke infection in combination with exposure to carcinogens. p53, a tumor suppressor, is the most mutated gene in human cancers including liver fluke-associated CCA. Hence, expression patterns of p53 and its target genes may be useful for diagnosis and/or prognosis of CCA patients. Methods: Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…RNA was extracted from liver tissues of CCA patients by coarsely homogenizing the tissue in TRIzol™ Reagent (Invitrogen) as previously described 43 . The RNA concentration and quality (260/280 ratio) were determined using a Nano Drop UV-spectrophotometer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…RNA was extracted from liver tissues of CCA patients by coarsely homogenizing the tissue in TRIzol™ Reagent (Invitrogen) as previously described 43 . The RNA concentration and quality (260/280 ratio) were determined using a Nano Drop UV-spectrophotometer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Toxoplasma infection regulates many cellular pathways to support its survival and proliferation. Many previous studies reported that the activation of P53 is associated with pathological changes in the cell, such as cell cycle arrest, oxidative stress, and DNA damage [ 8 , 9 , 56 ]. The important role of p53 in parasitic infectious diseases has been reported in previous studies [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two researchers performed the score evaluation. The immunohistochemical score (IHS) of each P53 and CD31 was calculated by multiplying the percentage of positive staining cells by the intensity degree of the stain and ranged from 0 (no immunoreactivity) to 12 (maximum immunoreactivity) [ 56 ]. The staining percentage was classified as follows: 0 = 0%, 1 = <10%, 2 = 10–25%, 3 = 26–50%, and 4 = 51–100%.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 13 somatic mutated genes were identified in plasma ctDNA, including ARID1A, PBRM1, MTOR, FGFR3, TP53, PTEN, NCOR1, EPHA2, PIK3CA, TERT, RASA1, EZH2 and BAP1. Mutations in ARID1A, BAP1, PBRM1, and TP53 were previously reported to be associated with poor prognosis for patients with cancer diseases [47][48][49][50]. ARID1A and PBRM1 encode a subunit of the SWI/SNF complex, and were mostly mutated in CCA, including association with tumor progression [48,49].…”
Section: Discussionmentioning
confidence: 99%